Analisis Strategi Pengembangan Usaha Ayam Potong Di Desa Bangun Rejo Gunung Sugih Lampung Tengah - Darmawan, Andre; Baskoro, Ery (Universitas Muhammadiyah Metro, 2022)
In the face of increasingly fierce business competition, businessmen are required to be able to develop their business appropriately. In business development there are a number of tasks and processes aimed at achieving good business opportunities. Chicken farming business is a type of business that has very good potential in the world economy. This study aims to determine matters related to internal factors (strengths and weaknesses) and external factors (opportunities and threats) as well as to determine the strategy for developing a broiler business in Bangun Rejo Village, Gunung Sugih District. The researcher used a qualitative research design. The subject of this research is the owner of a chicken slaughterhouse in Bangun Rejo Village, Kotagajah District. The object of this research is the analysis of the development strategy of the broiler business. Data collection techniques using interview and observation techniques. This research was analyzed using IFAS and EFAS methods, IE matrix, SWOT matrix. The results showed that the internal environmental conditions in the form of strength were high quality products, affordable prices, using direct distribution channels, very optimal promotions, high employee job satisfaction, conducive working conditions. The weakness of this business is that the products produced are less varied, the pricing is different, the delegation of tasks is still weak. External conditions concerning opportunities are able to increase job opportunities, increase people's income, get support from the community. While the threat is the presence of competitors. Keywords: Business Development, Chicken Slaughter, EFAS, IFAS, IE, SWOT.